Pencapaian Maslahah Melalui Etika Bisnis Islam Studi Kasus Restoran Mie Akhirat - Hidayat, Dany; Hasib, Fatin Fadhilah (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to understand the implementation of business ethics within the restaurantÂ âMie Akhiratâ. This Research uses a qualitative approach entailing a descriptive case study ofÂ the object and a purposive sampling technique. The data used are collected through a semistructuredÂ interview. Analysis of data is carried out by using the descriptive analysis model. TheÂ result of this research is expected to reveal the business ethics implemented within theÂ restaurant. This research hopes to benefit by exposing examples of islamic business ethicsÂ implemented by the restaurant. This research suggests that the implementation of islamicÂ business ethics would be of great benefit for the whole of society including their economiccondition.